2022
DOI: 10.1021/acs.est.1c06982
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth(III) Forms Exceptionally Strong Complexes with Natural Organic Matter

Abstract: The use of bismuth in the society has steadily increased during the last decades, both as a substitute for lead in hunting ammunition and various metallurgical applications, as well as in a range of consumer products. At the same time, the environmental behavior of bismuth is largely unknown. Here, the binding of bismuth­(III) to organic soil material was investigated using extended X-ray absorption spectroscopy (EXAFS) and batch experiments. Moreover, the capacity of suwannee river fulvic acid (SRFA) to enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…With that in mind, these data indicate that low concentrations of Bi were kept in the dissolved phase (<0.22 µm) due to complexation with DOC in the groundwater. The significant relationship observed between Bi and DOC in the groundwater agrees with the findings of [44], indicating that Bi forms very strong complexes with natural organic matter.…”
Section: Correlation Between Dissolved Bi and Doc In Groundwatersupporting
confidence: 85%
See 1 more Smart Citation
“…With that in mind, these data indicate that low concentrations of Bi were kept in the dissolved phase (<0.22 µm) due to complexation with DOC in the groundwater. The significant relationship observed between Bi and DOC in the groundwater agrees with the findings of [44], indicating that Bi forms very strong complexes with natural organic matter.…”
Section: Correlation Between Dissolved Bi and Doc In Groundwatersupporting
confidence: 85%
“…According to the sequential extraction from P4, higher concentrations of Bi were released from exchangeable phases throughout the tailings, indicating that either (1) 30%-40% of all Bi had been released from bismuthinite in the tailings and adsorbed as exchangeable fractions, or (2) bismuthinite is easily weathered in low-pH environments with high organic matter, which was the geochemical environment at the leaching step. A newly published paper by [44] showed that Bi forms exceptionally strong complexes with natural organic matter and with a wide range of organic acids. This supports alternative two, meaning that the acetic acid with a pH of 4 added in Step 2 likely affected the results of the sequential extraction.…”
Section: Bismuth Mobility In the Tailings And Transport To Groundwatermentioning
confidence: 99%
“…SEM and TEM show that BOC-3 consisted of microplates with a width of 1–3 μm and thickness of ∼200 nm (Figure a–f). It was proposed that Bi­(NO 3 ) 3 initially reacted with H 2 O to form [Bi 6 O 4 (OH) 4 (NO 3 ) 5 (H 2 O)]­(NO 3 ) and [Bi 6 O 4 (OH) 4 (NO 3 ) 6 (H 2 O) 2 ]·H 2 O precipitates, which then converted to BiOCl crystals during the hydrothermal treatment in the presence of Cl – at 160 °C . In contrast, BOC-1 and BOC-2 prepared in EG exhibited broad and weak XRD patterns (Figure g), indicating small size or poor crystallinity.…”
Section: Resultsmentioning
confidence: 99%
“…precipitates, which then converted to BiOCl crystals during the hydrothermal treatment in the presence of Cl − at 160 °C. 30 In contrast, BOC-1 and BOC-2 prepared in EG exhibited broad and weak XRD patterns (Figure 1g), indicating small size or poor crystallinity. As Bi(NO 3 ) 3 and NaCl could be completely dissolved in EG, the BiOCl nuclei formed and grew gradually at elevated temperatures, resulting in nanosheets with a diameter of ∼100 nm.…”
Section: T H Imentioning
confidence: 95%
“…Solution pH and the presence of citric acid, tartaric acid, L-cysteine, and soil humic acids influenced bismuth solubility. Kleja et al [18] investigated the binding of Bi3+ to organic soil materials and noted that Bi3+ formed organic soil complexes, forming a dimeric Bi3+ complex.…”
Section: Introduction To Bismuthmentioning
confidence: 99%